Initial Crack Analysis on 175 Nm Torque Differential Helical Gear Using Finite Element Method for Structural Failure Prediction - Fauzan, Fauzan; Harmin, Amalia; Isra, Muhammad; Rizqullah, Akbar; Rizki, Muhammad Nuzan (E-Journal Universitas Malikussaleh, 2025)
Differential helical gears are critical components in power transmission systems of vehicles, responsible for transmitting torque from the engine to the drive wheels. These components operate under continuous high torque loads and are susceptible to failure due to material fatigue and the presence of initial cracks. This study aims to predict the initial crack location and evaluate the potential failure of a differential helical gear subjected to a 175 Nm torque using the Finite Element Method (FEM). The gear was modeled with actual dimensions and simulated using ANSYS software under two conditions: without cracks and with an initial crack. The simulation results show that the maximum shear stress without a crack is 45.82 MPa, while with an initial crack, it increases to 66.14 MPa, exceeding the allowable shear stress of ASTM A36 material at 45.45 MPa. This significant increase in stress due to the crack indicates a high risk of structural failure. Therefore, finite element analysis proves to be an effective tool for early crack detection and stress distribution evaluation, which is essential for improving the reliability of gear design and material selection.